Role of Wildlife Conservation on Socio-Economic Development of Households: A Case Study of Muramba Sub-County Kisoro District. - Turinayo, John (Kabale University, 2024)
Wildlife conservation is a crucial aspect of sustainable development in Uganda, particularly in regions such as Muramba Sub-County, and Kisoro District, where communities rely on natural resources for their livelihoods. This study explores the role of wildlife conservation on the socio-economic development of households in Muramba Sub-County, focusing on the benefits, challenges, and opportunities associated with conservation efforts. Utilizing qualitative research methods, including interviews, field observations, and analysis of secondary data, information was gathered from local residents, conservation experts, and community leaders. The findings reveal that wildlife conservation contributes to socio-economic development by promoting tourism, providing employment opportunities, and enhancing community infrastructure. However, challenges such as human-wildlife conflicts, inadequate community involvement, and limited access to conservation benefits were identified. The study highlights the importance of community engagement in wildlife conservation initiatives to maximize socio-economic benefits. It emphasizes the need for conservation strategies that include local communities, promote environmental awareness, and ensure equitable distribution of tourism revenues. Furthermore, the research identifies opportunities for collaboration between government agencies, conservation organizations, and local communities to foster sustainable wildlife conservation while improving the socio-economic conditions of households. This research contributes to a better understanding of the link between wildlife conservation and socio-economic development in Muramba Sub-County and provides valuable insights for policymakers, conservation practitioners, and community leaders in developing inclusive and sustainable conservation strategies in Kisoro District and beyond.